RESPON VARIETAS WIJEN (SESAMUN INDICUM, L.) WINAS 1 DAN WINAS 2 TERHADAP ARANG AKTIF DALAM MEDIA TANAH PASIR - Dewi Ratna Nurhayati Martana (RESEARCH FAIR UNISRI, 2018)
One of the obstacles in the cultivation of plants is the condition of the rightplanting media, which is supported by the availability of water and nutrients for plants.In order to increase the productivity of the plant, it needs applied technology so that thephysical, chemistry and biological planting conditions are met for plant growth anddevelopment through the use of active charcoal-based soil enhancers that have thepotential to improve the biological soil amendments. So as to optimize the planting mediato the physical properties of soil, chemical, biological, can hold water and providenutrients, which then make it as a source of sustainable plant needs in sesame plants. Thisresearch will be carried out in the experimental garden. FP Unisri in February - September2017. The design used was Completely Randomized Design (RAL) with 3 replications.Treatment factors such as sesame varieties and combination of active charcoal soilenhancers. The varieties used are Winas 1 and Winas 2. Combinations of soil enhancersfor soil type sand, treatment (100 g of activated charcoal, 100 g of activated charcoal + 100g of manure, 200 g of activated charcoal, 200 g + 100 g manure). The observations were:agronomic observation on the growth vase of sesame plant (60-70 HST), the resultsshowed that 200g of active char and 100 g of fertilizer could increase the growth of sesamewinas 2.Keywords: active charcoal, Biological Soil Amendments, soil fertility observation, physiological andagronomic parameters.